Teknik genetika modern: Pemanfaatan stem cells dalam dunia medis dan bagaimana pandangan Islam terkait teknik ini - Ayun, Ziskino Qurota (Maliki Interdisciplinary Journal, 2024)
Stem cells are stem cells that have not undergone differentiation or maturity, can reproduce themselves, and replace damaged cells. The development of stem cell therapy can have a major impact on the world of health, especially the treatment of degenerative diseases, cancer treatment, and repair of damaged cells. However, there are pros and cons from researchers regarding some of the applications of stem cell therapy because it is based on applicable Islamic law.